A transanal procedure using TST STARR Plus for the treatment of Obstructed Defecation Syndrome: 'A mid-term study'. (August 2016) - Ren, X.H.; Yaseen, S.M.; Cao, Y.L.; Liu, W.C.; Shrestha, S.; Ding, Z.; Wu, Y.H.; Zheng, K.Y.; Qian, Q.; Jiang, C.Q.
Abstract: Purpose: The aim of this study was to assess the safety, efficacy and outcomes of TST STARR (Stapled Transanal Rectal Resection) plus to treat Obstructed Defecation Syndrome (ODS) at mid-term follow-up. Methods: From April 2013 to September 2014, 50 cases (7 male patients) with ODS caused by rectocele and/or internal rectal prolapse were treated with the new TST STARR Plus. Clinical data from the 18 month mid-term follow up, including efficacy and constipations were recorded. Results: The average duration of surgery was 21 ± 4 min (range 12–35 min). The average postoperative hospital stay was 5 days (range 4–8 days). The pathological findings showed that the specimens contained full-thickness rectal tissue in all patients. The mean volume of resected specimen was 12.3 cm 3 . Postoperative complications included five cases with transient faecal urgency that dissipated after 3 months; one patient suffered anastomotic bleeding on the sixth day after surgery, with successful haemostasis achieved through conservative therapy. The Wexner constipation score improved in patients affected by ODS from 13.96 ± 2.37 preoperatively to 7.00 ± 3.90, 7.28 ± 3.91, 8.10 ± 4.05 and 8.44 ± 4.08 at 3, 6, 12 and 18 months postoperatively, respectively, with all p  < 0.05. Overall outcome was reported as ''excellent'' in 42% of patients, ''good'' in 36% of patients, ''adequate'' in 12% of patients, and ''poor'' in 10% of patients after 18 months of follow-up. Conclusions: The TST STARR Plus is a simple, safe, and effective option for selected patients with ODS. Long-term prospective clinical studies are needed to validate the advantages of this emerging, novel procedure. Highlights: The first mid-term follow-up of TST STARR Plus for Obstructed Defecation Syndrome. 50 patients with Obstructed Defecation Syndrome were treated with the new TST STARR Plus device, a novel surgical procedure. At 18 months, the majority of patients obtained a good curative effect, improved symptoms significantly and was "satisfied" with the efficacy of treatment by utilizing this new device.